Successful pregnancy in a woman of late reproductive age with type 1 diabetes mellitus after combined pancreas — kidney transplantation - E. I. Prokopenko; F. F. Burumkulova; I. G. Nikolskaya; T. S. Kovalenko; V. A. Petrukhin (Сахарный диабет)
Women of reproductive age with type 1 diabetes mellitus (DM) and chronic kidney disease stage 5 after successful combined pancreas-kidney transplantation (CPKT) can experience spontaneous pregnancies with a favorable outcome. However, those pregnancies are associated with a high risk of complications: arterial hypertension, preeclampsia, premature birth, progression of diabetic retinopathy. During pregnancy, both gestational diabetes and spontaneous hypoglycemia can develop. This article presents a description of the clinical case of a 42-year-old patient with DM type 1, in whom pregnancy occurred 2 years after successful CPKT. Blood pressure was normal, the fundus condition was stable after previous treatment. The patient received tacrolimus and minimal dose of corticosteroids, at 13 weeks acetylsalicylic acid was prescribed to prevent preeclampsia. At 30 weeks nocturnal episodes of hypoglycemia appeared that were treated by additional intake of carbohydrates with an average glycemic index in combination with animal fats and proteins. At 36 gestational weeks caesarean section was performed due to premature rupture of membranes. A healthy girl was born with weight of 2140 g, height of 48 cm, Apgar score 7/8 points. The mother’s function of the kidney and pancreas grafts remained normal. Preconceptional counseling and multidisciplinary pregnancy management are important for patients after CPKT.